High-fat, sucrose and salt-rich diet during rat spermatogenesis lead to the development of chronic kidney disease in the female offspring of the F2 generation - Zhang, Xiaoli; Hasan, Ahmed A.; Wu, Hongwei; Gaballa, Mohamed M. S.; Zeng, Suimin; Liu, Liping; Xie, Li; Jung, Tobias; Grune, Tilman; Krämer, Bernhard; Kleuser, Burkhard; Li, Jian; et al. (The FASEB journal, 2022)
Effects of feeding male rats during spermatogenesis a high-fat, high-sucrose and high-salt diet (HFSSD) over two generations (F0 and F1) on renal outcomes are unknown. Male F0 and F1 rats were fed either control diet (F0CD+F1CD) or HFSSD (F0HD+F1HD). The outcomes were glomerular filtration rate and urinary albumin excretion in F1 and F2 offspring. If both outcomes were altered a morphological and molecular assessment was done. F2 offspring of both sexes had a decreased GFR. However, increased urinary albumin excretion was only observed in female F2 F0HD+F1HD offspring compared with controls. F0HD+F1HD female F2 offspring developed glomerulosclerosis (+31%; p < .01) and increased renal interstitial fibrosis (+52%; p < .05). RNA sequencing followed by qRT-PCR validation showed that four genes (Enpp6, Tmem144, Cd300lf, and Actr3b) were differentially regulated in the kidneys of female F2 offspring. lncRNA XR-146683.1 expression decreased in female F0HD+F1HD F2 offspring and its expression was (r = 0.44, p = .027) correlated with the expression of Tmem144. Methylation of CpG islands in the promoter region of the Cd300lf gene was increased (p = .001) in female F2 F0HD+F1HD offspring compared to controls. Promoter CpG island methylation rate of Cd300lf was inversely correlated with Cd300lf mRNA expression in F2 female offspring (r = −0.483, p = .012). Cd300lf mRNA expression was inversely correlated with the urinary albumin-to-creatinine ratio in female F2 offspring (r = −0.588, p = .005). Paternal pre-conceptional unhealthy diet given for two generations predispose female F2 offspring to chronic kidney disease due to epigenetic alterations of renal gene expression. Particularly, Cd300lf gene promotor methylation was inversely associated with Cd300lf mRNA expression and Cd300lf mRNA expression itself was inversely associated with urinary albumin excretion in F2 female offspring whose fathers and grandfathers got a pre-conceptional unhealthy diet.